New insights into methylmercury induced behavioral and energy-related gene transcriptional responses in European glass eel (Anguilla anguilla). (September 2020) - Liu, Hengtong; Lamarins, Amaia; Labonne, Jacques; Monperrus, Mathilde; Coste, Pascale; Huchet, Emmanuel; Rives, Jacques; Seiliez, Iban; Bolliet, Valérie
Abstract: The effect of methylmercury (MeHg) was investigated in glass eel migration behavior and metabolism. To migrate up estuary, glass eels synchronize their swimming activity to the flood tide and remain on or in the substratum during ebb tide. Following seven days of exposure to MeHg (100 ng L −1 ), glass eels migration behavior was expressed by their swimming synchronization to the water current reversal every 6.2 h (mimicking the alternation of flood and ebb tides) and their swimming activity level. In relation to their behavior, we then analyzed the energy-related gene expression levels in individual head, viscera and muscle. Results showed that MeHg decreased the number of glass eels synchronized to the change in water current direction and their swimming activity level. This last effect was more pronounced in non-synchronized fish than in synchronized ones, supporting the idea that non-synchronized glass eels could be more vulnerable to stress. As regard the expression of energy-related genes, no significant difference was observed between control and MeHg-exposed fish. In contrast, when the swimming activity levels were plotted against transcriptional responses, positive correlations were evidenced in viscera and especially in the head of exposed glass eels but not in control. Finally, it is noteworthy that non-synchronized glass eels displayed lower expression level of metabolism genes than their synchronized counterpart, but only in the head. Altogether, these results support the interest of focusing on the head to investigate the facultative migration behavior in glass eels and the effect of environmental stressors on this rhythmic behavior. Graphical abstract: Image 1 Highlights: MeHg decreased the swimming activity level in glass eels. The effects of MeHg were stronger in individuals that did not synchronize to the tide. MeHg affected the relation between metabolism-related genes and swimming activity. MeHg mainly targeted the head and viscera in glass eels.